Women and children in the media : the presence of women; their administrative status; and the voices of children - Davis, Karen (Guyana. Ministry of Labour, Human Services and Social Security; National Resource and Documentation Centre in collaboration with UNICEF GeorgetownGY, 2015)
Examines the presence and administrative status of women in the media in Guyana, and the voices of children.